Analysis of determinant diabetic neuropathy symptom score factors in diabetes mellitus patients - Nurul Aktifah; Umi Budi Rahayu; Muhammad Ghilang Maulud Setyawan; Firman Faradisi; Dwi Fijianto (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2023)
Background: Diabetes peripheral neuropathy (DPN) is a set of signs and symptoms of peripheral nervous system dysfunction in diabetes mellitus patients. Abdominal obesity is one of the main risk factors for DPN. Diabetic neuropathy symptom (DNS) is a reliable instrument with consistent results for the diagnosis of neuropathy. Objective: This study aimed to determine the correlation of abdominal obesity with scores. Methods: This research was a quantitative study with a cross-sectional approach. The sample of this study was 92 type 2 diabetes mellitus (T2DM) patients aged range 30-60 years who participated in the chronic disease management program (Prolanis) and the integrated healthcare center (Posbindu) for people in the area of three public health centers (Puskesmas) in Pekalongan Regency which purposively selected. Instruments used to measure DPN were DNS sheets, and abdominal obesity was measured by waist circumference using a midline. The bivariate analysis was performed using the Pearson correlation and linear regression tests. Results: There was a correlation between abdominal obesity and DNS scores with a p value of 0.043 with a correlation coefficient of 0.212. The DNS score was influenced by age, gender, duration of diabetes, and body mass index by 13.4%. Conclusion: There was a correlation between abdominal obesity and DNS scores. It indicated that the higher the value of abdominal obesity was, the higher DNS scores increased.